An investigation of pressure build-up effects due to check valve's closing characteristics using dynamic mesh techniques of CFD. (March 2021) - Kim, Nam-Seok; Jeong, Yong-Hoon
Highlights: Four different dynamic mesh methods are simulated. Strategies to describe the full closure of the valve has been proposed. The prediction of inflowing fluid velocity at the closure are compared and discussed. Abstract: The present study provides recommendations for choosing the appropriate moving mesh techniques of CFD to describe the dynamic behavior of a check valve and to evaluate a pressure build-up in response to the valve's closing behavior. Four different moving mesh techniques of CFD were modeled and compared, and the compressibility of the fluid was involved in simulating the pressure build-up by valve closing. The results showed that the swing check valve's dynamic behavior during the valve closure could be well described by the moving mesh techniques presented in this study because the velocity profiles at the outlet of each method were similar until the valve was almost closed. However, even though the moving mesh techniques described the check valve's closing behavior well, the predictions of the inflowing fluid velocity at the moment when the valve was fully closed were different from one another.